2022
DOI: 10.1177/17454999211066183
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of financial literacy levels and initiatives among students in five European countries

Abstract: Given the expected advantages for individuals and societies, financial literacy is high on the policy agenda in many countries. This paper reports the results from a unique survey conducted on a sample of 13–16-year-old students in five European countries, aimed at measuring and comparing their level of financial literacy skills. The results indicate significant differences in the level of financial literacy across countries that are interpreted in the light of the differences in the countries’ educational pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, a high income can also lead to financial knowledge overconfidence as reported by Ansari et al (2023). Previous studies found differences in the level of financial literacy across countries that were interpreted as a result of differences in countries' educational policies (Cannistr a et al, 2022), which suggests that the education level could be a predictor of their financial literacy. Chen et al (2018) also suggest that, when investors work in the finance or information technology industries, there are more similarities between female and male investors.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 96%
“…However, a high income can also lead to financial knowledge overconfidence as reported by Ansari et al (2023). Previous studies found differences in the level of financial literacy across countries that were interpreted as a result of differences in countries' educational policies (Cannistr a et al, 2022), which suggests that the education level could be a predictor of their financial literacy. Chen et al (2018) also suggest that, when investors work in the finance or information technology industries, there are more similarities between female and male investors.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 96%